Pendekatan Pembelajaran PIESQ pada Siswa di Sekolah Alam Nur Hikmah dalam Perspektif Teori AGIL - Grenada Tri Kardiana; Seli Septiana Pratiwi (Faculty of Social Science, Universitas Negeri Malang, 2022)
SANHIKMAH's natural school has the advantage of implementing PIESQ-based learning to accommodate different student learning needs. The focus of this research is on the implementation of the PIESQ approach through the teacher's role in implementing this approach in the classroom. The purpose of this research is to show and describe the application of the PIESQ approach in the SANHIKMAH natural school. Descriptive qualitative was used in this study to obtain in-depth data related to the research topic obtained through observation, interviews and documentation. The resource persons involved were class teachers, students, parents, and the Director of the SANHIKMAH Foundation. The selection of informants used purposive sampling with several criteria set by the researcher. The AGIL theory of Talcott Parsons is used by researchers as an analytical knife. The results of the study show (a) the application of PIESQ learning is carried out through Physical, Intellectual, Emotional, Spiritual, and Quotient activities; (b) there are factors driving and inhibiting the success of PIESQ-based learning as seen from school infrastructure, teaching staff, cooperation and concern for parents, as well as activities supporting PIESQ understanding for teachers, parents, and students; (c) student learning outcomes show that there are teacher differences in determining the basis of assessment between students with special needs and normal, besides that there are 2 forms of reports submitted to guardians, namely the PKBM and SKB formats, as well as the PIESQ report card form containing photo documentation of activities and descriptions of activities in detail detailed and clear.